Theoretical analysis of nitroxide-mediated copolymerization of styrene and a-methyl-styrene under different operating policies and reactor designs - Fortunatti, Cecilia (2013)
The polymerization that IUPAC terms reversible-deactivation radical polymerization is a controlled radical polymerization technique (CRP) that allows producing polymers with tailored properties without the stringent conditions typical in ionic polymerization. A theoretical analysis is presented of the influence of operating and design conditions on the product properties for the nitroxide-mediated copolymerization (NMP) of styrene and α-methyl styrene. Several reactor configurations are analyzed, with different feeding policies and temperature profiles. To this end a mathematical model is developed to predict copolymer average properties and the complete bivariate MWD. The results help establishing design parameters and optimal operating policies to obtain desired copolymer microstructures.